2015
DOI: 10.3892/ijmm.2015.2160
|View full text |Cite
|
Sign up to set email alerts
|

miR-204-5p promotes the adipogenic differentiation of human adipose-derived mesenchymal stem cells by modulating DVL3 expression and suppressing Wnt/β-catenin signaling

Abstract: MicroRNAs (miRNAs or miRs) play an important regulatory role during adipogenesis, and have been studied extensively in this regard. Specifically, the switch between the differentiation of mesenchymal stem cells (MSCs) towards adipogenic vs. osteogenic lineages is regulated by miR-204 which controls the expression of Runx2. However, the association between miR-204-5p and the Wnt/β-catenin signaling pathway during adipogenesis has not yet been clarified. In the present study, we demonstrate that miR-204-5p regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…Conversely, because basal miR-204 levels are higher in MAPC, the effects of miR-204 downregulation by transfecting MAPC with a miR-204 inhibitor were investigated. A number of publications have demonstrated that miR-204 plays a role in cell differentiation [43][44][45][46][47], and although effects may be cell-typedependent [44], a consistent positive effect of miR-204 on adipocyte differentiation had been described [43,47]. Consistent with these previous publications, knockdown of miR-204 in MAPC led to reduced adipocyte differentiation of MAPC as demonstrated by Oil-Red-O staining (Fig.…”
Section: Validation Of Mirna Function In Establishment Of Mapc Characsupporting
confidence: 83%
See 1 more Smart Citation
“…Conversely, because basal miR-204 levels are higher in MAPC, the effects of miR-204 downregulation by transfecting MAPC with a miR-204 inhibitor were investigated. A number of publications have demonstrated that miR-204 plays a role in cell differentiation [43][44][45][46][47], and although effects may be cell-typedependent [44], a consistent positive effect of miR-204 on adipocyte differentiation had been described [43,47]. Consistent with these previous publications, knockdown of miR-204 in MAPC led to reduced adipocyte differentiation of MAPC as demonstrated by Oil-Red-O staining (Fig.…”
Section: Validation Of Mirna Function In Establishment Of Mapc Characsupporting
confidence: 83%
“…They have also been reported to be downregulated in aging cells, including MSCs [57]. As mentioned previously, miR-204 is known to regulate both osteoblast and adipocyte differentiation in vitro [43][44][45][46][47], but has also been associated with adipose tissue development in vivo [58,59]. Additionally the MAPC marker miR-155 has been shown to exert immune-modulatory functions in T cells, B cells, and dendritic cells [60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, miR-204 is a “switch” molecule that controls the fate choice between osteogenesis and adipogenesis [9]. Consistently, miR-204 promotes the differentiation of human adipose-derived MSCs into mature adipoctyes [10]. Moreover, disheveled segment polarity protein 3 (DVL3), a key regulator of the Wnt/β-catenin signaling pathway, was identified as the target of miR-204.…”
Section: Physiological Functions Of Mir-204mentioning
confidence: 99%
“…In addition, overexpression of miR-204 was shown to induce the downregulation of β-catenin and the canonical Wnt target gene, CCND1, in mature adipoctyes, while its knockdown led to upregulation of CCND1. Therefore, miR-204 was proposed to regulate adipogenesis by controlling DVL3 expression and subsequently inhibiting the activation of the Wnt/β-catenin signaling pathway [10]. …”
Section: Physiological Functions Of Mir-204mentioning
confidence: 99%
“…Relatively little is known of the impact of post-transcriptional regulation of Dvl on Wnt signaling pathways (He et al, 2015;Huang et al, 2018). MicroRNAs (miRNAs) are small non-coding RNAs that regulate post-transcriptional gene expression by binding to the 3′ untranslated region (3′UTR) of target mRNAs to repress their translation and/or induce mRNA degradation (Bartel, 2009).…”
Section: Introductionmentioning
confidence: 99%